Morir en el Valle de San Francisco. Prácticas funerarias, termoalteración y estratégias de memorización en la selva pedemontaña de las Yungas del Noa - Ortiz, Gabriela; Nieva, Luis (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The thermal alteration associated with human remains in prehispanic contexts of South America is not uncommon. In relation to this type of burial custom many interpretations have been given, ranging from the preservation of the body in order to perform double funerals, to the ingestion of human remains in contexts of anthropophagic practices. This paper presents new data related to the mortuary diversity in populations of San Francisco tradition of the Yungas or mountain rainforest of Jujuy, Argentina (800 B. C.–500 A. D.), especially those involving heat treatment of bone remainders. Contextual associations of the fi ndings are discussed by comparing them with other registered at different sites in the region in more than one century of discontinuous research. The information comes especially from exhumation contexts at the site Pozo de la Chola.The article will be available as a PDF in the near future.